New solutions to the generalized (2+1)-D Boiti–Leon–Pempinelli equation - Sabi'u, Jamilu; Gomez S, Cesar A.; Rezazadeh, Hadi; İnç, Mustafa (Shanghai Jiaotong University, 2022)
In this article, we will study the (2 + 1)-D Boiti–Leon–Pempinelli (BLP) model, which has an application in hydrodynamics. This model explains the evolution of water waves in hydrodynamics. We obtained new explicit solutions to the generalized (2 + 1)-D BLP equation using the improved tanh-coth method. This method proves to be a reliable and effective tool for solving nonlinear wave equations. Furthermore, different solitary wave solutions are constructed such as dark, bright, and kink solitons. The variable-coefficient models are more generic than their constant-coefficient counterparts are, the reported for the variable coefficient BLP equation are stable and different relative to those achieved using other techniques. © 2022
Keywords: Coupled Boiti–Leon–Pempinelli system; Improved tanh-coth technique; Periodic solutions; Solitons